Mechanical Properties of Unsaturated Polyester Filled With Silica Fume, Glass Powder and Carbon Black - A.H. Majeed; S.Q. Ibrahim (Engineering and Technology Journal, 2017)
In this study a polymer matrix composites (PMCs) have been prepared with the aid of ultrasonic wave dispersion method for mixing , using of unsaturated polyester resin with Silica Fume(SF), Glass Powder (GP)and Carbon Black (CB). Moulds were prepared by hand-made from silicon rubber according to the ASTM standard table (4). The fillers added separately with different ratios as (0%,0.5%, 1%, 1.5 %, 2%,2.5% and 3%).The results show increase the hardness and impact strength when added GP, SF, and CB to polymer matrix. Flexural strength and maximum shear stress decrease when added silica fume , but when added glass powder and carbon black led to increase flexural strength and maximum shear stress to certain percent at ( 2%, 1.5% for GP and CB respectively) then dropped when increase weight fraction of GP, CB . Compressive strength decrease when added glass powder and carbon black, while it is increase when added silica fume to polymer matrix. Wear rate decrease when increase weight fraction of carbon black but it increases when added GP and SF.